(E)-4-Bromo-2-[2-(Hydroxymethyl)-Phenyliminomethyl]Phenol - Köysal, Y.; Işík, S.; Aǧar, A. (Blackwell Publishing, 2007)
The title compound, C14H12BrNO2, adopt the phenol-imine tautomeric form. The dihedral angle between the aromatic rings is 27.49 (2)°. In the structure, there are O - H⋯O inter-molecular hydrogen bonds and O - H⋯N and C - H⋯O intra-molecular hydrogen bonds. The phenol H atom forms a strong intra-molecular hydrogen bond with the imine N atom. © International Union of Crystallography 2007.